2010
DOI: 10.1590/s1679-45082010rw1311
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory assessment in daily clinical practice - not yet ready but not too far!

Abstract: Shock is characterized by an alteration in tissue perfusion that may lead to tissue hypoxia. Recent guidelines recommend aggressive and early resuscitation therapy, but mortality rate is still unacceptably high. Unfortunately, traditional clinical surrogates used to guide resuscitation therapy poorly correlate with microcirculatory blood flow, a key determinant of tissue perfusion. New techniques that directly assess microcirculatory perfusion at the bedside have emerged as a complement to traditional macrohem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
4
0
3
Order By: Relevance
“…Meanwhile, there was no obvious difference observed between the MMBF in MTrPs of the two groups. A study related to sepsis found that microcirculatory alterations can be detected in very early stages of the disease and may persist regardless of the macrohemodynamic status [ 11 , 30 , 31 ]. Those findings were consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there was no obvious difference observed between the MMBF in MTrPs of the two groups. A study related to sepsis found that microcirculatory alterations can be detected in very early stages of the disease and may persist regardless of the macrohemodynamic status [ 11 , 30 , 31 ]. Those findings were consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to assess shoulder and neck pain include the visual analogue scale (VAS) score [ 5 ], Neck Disability Index, neck mobility, muscle strength [ 6 , 7 ], white-light spectroscopy, Laser Doppler Flowmetry (LDF) [ 8 , 9 ], and quantitative imaging biomarkers [ 10 ]. Salgado [ 11 ] discussed several techniques for evaluating microvasculature perfusion, such as LDF, intravital microscopy, and orthogonal polarization spectral imaging techniques. The capillary refill time constitutes an accessible route for probing microcirculation, which is applied during shock resuscitation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early or large-volume resuscitation in severe hemorrhage has not been supported by randomized controlled trials so far [9]. Increased hemorrhage volume and markedly higher mortality may ensue following 'classical' high-volume, normotensive resuscitation in case of major vascular injury [9,10]. In a study of uncontrolled hemorrhage, infusion of only enough fluid to maintain a MAP of 40 mm Hg improved survival rates and decreased hemorrhage [11] withholding of intravenous fluids in severe shock resuscitation still needs to be studied [12].…”
Section: Small Volume Rsuscitation or "Permissive Hypotension"mentioning
confidence: 99%
“…Οι διαφορετικού βαθμού διαταραχές της μικροκυκλοφορίας έχουν ως αποτέλεσμα την υποάδρευση και την ανεπάρκεια των ιστών και έχουν συσχετιστεί με τη νοσηρότητα και τη θνησιμότητα σε διάφορες παθολογικές καταστάσεις όπως π.χ. στην σήψη και στον διαβήτη[76,78,84]. Η μικροκυκλοφορία μπορεί να εξεταστεί ευκολότερα στην περιφέρεια, π.χ.…”
unclassified
“…Ο έλεγχος της αιματικής ροής γίνεται με τους προτριχοειδικούς σφιγκτήρες, οι οποίοι επηρεάζονται εν μέρει από συστημικούς παράγοντες, τη συμπαθητική διέγερση και διάφορα κυκλοφορούντα στοιχεία[74]. Τα κύρια είδη κυττάρων που εμπλέκονται στην μικροκυκλοφορία είναι τα ερυθρά και λευκά αιμοσφαίρια, τα αιμοπετάλια, τα κύτταρα του λείου μυϊκού ιστού και τα ενδοθηλιακά κύτταρα[77,78].6. Μέθοδοι εκτίμησης της μικροκυκλοφορίαςΗ βιντεομικροσκοπία και το σύστημα Λέιζερ Ντόπλερ (Laser Doppler)[84].…”
unclassified